The Routledge Handbook of Policy Tools - Howlett, Michael (Taylor & Francis, 2023)
This handbook provides a unique, systematic and comprehensive overview from leading experts in the field of the policy-making tools deployed at all the phases of the policy process. It covers the fundamentals of both new and established policy tools - from regulation and public enterprises to subsidies and information campaigns, as well as new tools such as, social impact investing, nudges, crowdsourcing, co-production and new digital governance and data analysis techniques. The book consists of nine sections with five corresponding to the major research emphases of studies on policy tools across the stages of the policy cycle (agenda-setting, formulation, decision-making, implementation and evaluation). These are accompanied by overviews of key research and concepts, a discussion of how different kinds of tools can be usefully combined in simple or complex policy portfolios or mixes, and a concluding section on future research directions. Consolidating the state of knowledge, and uniting classic foundational material with recent advancements in theory and practice in one location, the handbook is a defining volume in this field. The Routledge Handbook of Policy Tools is essential reading and an authoritative reference for scholars, students, researchers and practitioners of Public Policy, Public Administration, Public Management as well as those interested in Comparative Politics and Government, Public Organizations and the use of policy tools and instruments in individual policy areas from climate change to public health.